Near-infrared light polymerization composite hydrogel as well as preparation method and application thereof
By introducing rare earths into the hydrogel to convert nanoparticles, and using 808nm near-infrared light excitation to generate ultraviolet light, the problems of shallow penetration of light-responsive hydrogels and poor photothermal effects in the prior art are solved, and trauma to deep tissues is achieved Efficient repair.
Patent Information
- Application Number
- CN202411300211.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing light-responsive hydrogels have shallow penetration under ultraviolet excitation and have poor photothermal effects, making it difficult to effectively repair deep tissue trauma.
Develop a near-infrared photopolymerization composite hydrogel, which uses rare earth up-converting nanoparticles to excite under 808nm near-infrared light, and generates ultraviolet light that can be absorbed by photoinitiators through the inverse-Stokes energy transfer process to cure water Gels that promote deep tissue trauma repair.
It improves the penetration depth and curing efficiency of the hydrogel, reduces the photothermal effect, and achieves effective repair of deep tissue trauma.
Smart Images

Figure CN119161597A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wound repair, and in particular to a near-infrared photopolymerized composite hydrogel and a preparation method and application thereof. Background Art
[0002] Wound infection is one of the most common health problems in clinical practice, and the cost of wound care and healing has continued to increase in the past few years. Therefore, rapid and effective wound healing is crucial to saving lives. Effective management of the wound surface can prevent infection and promote effective tissue regeneration. Dressings can not only prevent pathogens and any harmful substances from entering, but also help wounds heal quickly.
[0003] Traditional wound dressings such as gauze, bandages, cotton balls and other materials are used to inhibit the occurrence of secondary injuries at the wound site. They are widely used because of their convenience, low cost and simple manufacturing. Although these dressings can protect wounds from external infection, they cannot control the hygroscopicity of the wound, resulting in excessive dryness of the wound and failure to heal in time. In addition, in the case of excessive wound drainage, they may adhere to the wound, resulting in a complicated and painful dressing removal process. With the advancement and development of science and technology, many modern dressings have been invented, such as semi-permeable membranes, alginate, tissue adhesives, hydrogels, etc. These dressings are characterized by good elasticity, easy application and removal, and rehydration of the wound. Among them, hydrogels have attracted the attention of scholars. It is a hydrophilic polymer material with a mesh structure that combines the characteristics of natural and synthetic materials. In terms of the source of raw materials, hydrogels extracted from natural resources such as hyaluronic acid, collagen, gelatin, chitosan, etc. have excellent biocompatibility and degradability, and are therefore widely used in the biomedical field.
[0004] As a wound dressing, hydrogel can overcome the limitations of traditional dressings in clinical applications. Its high water content can provide a suitable moist environment for the wound site and promote wound healing. Secondly, the advantages of hydrogels are also reflected in their sustainable absorption of wound exudates to prevent secondary infection, and their transparent or translucent state makes it easy to monitor the progress of wound healing. In addition, hydrogels encapsulated with specific drugs can gradually and continuously release drugs at the wound site to promote wound healing. At the same time, hydrogel dressings can also protect wounds and relieve pain to a certain extent. The above characteristics make hydrogel-based dressings one of the most competitive functional materials in medical fields such as wound care and tissue regeneration in the past few decades. Hydrogels are used as wound dressings and can be used as carriers for controlled drug delivery, so that therapeutic agents can be released in a targeted manner to the wound site, thereby achieving tailored treatment and optimal healing conditions. Several common response modes are: temperature-dependent, enzyme-responsive, pH-responsive, light-responsive, etc. Due to the chemical and physical diversity of hydrogels, light-responsive hydrogels have become an ideal choice. That is, the process of using light to trigger a chemical reaction, that is, through the irradiation of light of a certain wavelength and intensity, the photosensitive substance in the material will absorb the light energy and convert it into excited energy, causing the molecular structure of the hydrogel material to change, thereby achieving the curing effect. The advantages of this light control are: the light is non-invasive, and the by-products are limited in the absence of additional reagents, avoiding pollution to the environment; the process is controllable, and the light parameters and the concentration of the photosensitive substance can be adjusted as needed; the process is efficient, and curing can be completed with a short period of light exposure, which improves production efficiency.
[0005] However, due to the limitation of photosensitive materials, most of them choose light in the ultraviolet region for excitation to complete photopolymerization. Taking ultraviolet light curing as an example, hydrogel materials cured after light irradiation can provide a suitable microenvironment for wounds to treat trauma and repair incisions. However, there are also problems: light in the ultraviolet region has a shallow penetration depth in biological tissues due to absorption and scattering problems, and short wavelengths can cause some biological safety issues to biological tissues. Recent studies have pointed out that using X-rays as an excitation source can enhance the penetration depth, but the radiation effect of high-energy rays on the organism itself cannot be ignored. To address this problem, the near-infrared biological window excitation strategy can be used as a reference. Since water and biological tissues have low absorption of light in the near-infrared region, the penetration depth of near-infrared light is deeper. In recent years, upconversion nanoparticles (UCNPs) have become promising materials for wound dressing applications due to their unique optical properties and potential therapeutic functions. These nanoparticles can be combined with other materials such as hydrogels. The photons absorbed by the photoinitiator specifically promote the breaking of chemical bonds under light irradiation, generating active free radicals, while the free radicals and related functional groups present in the prepolymer monomers promote the establishment of chemical cross-links between monomers, enabling the hydrogel to provide a suitable microenvironment at the wound to block bacterial invasion.
[0006] The present invention intends to develop an 808nm near-infrared photopolymerizable composite hydrogel to solve the problems of shallow tissue penetration and poor photothermal effect of existing photoresponsive hydrogels. Summary of the invention
[0007] The purpose of the present invention is to provide a near-infrared photopolymerized composite hydrogel and its preparation method and application to solve the problems existing in the above-mentioned prior art. Near-infrared light can excite the rare earth upconversion nanoparticles in the composite hydrogel, and the luminescent ions therein emit ultraviolet light that can be absorbed by the photoinitiator, thereby curing the composite hydrogel and achieving the purpose of promoting the repair of deep tissue wounds.
[0008] To achieve the above object, the present invention provides the following solutions:
[0009] The invention provides a method for preparing a near-infrared photopolymerized composite hydrogel, comprising the steps of uniformly mixing hydrophilic upconversion nanoparticles and methacrylated gelatin in a solvent to obtain the near-infrared photopolymerized composite hydrogel.
[0010] Furthermore, the hydrophilic upconversion nanoparticles are obtained by contacting upconversion nanoparticles with NOBF4.
[0011] Furthermore, the upconversion nanoparticles are NaYF4:Yb 3+ ,Tm 3+ Nanoparticles or NaYF4:Yb 3+ ,Tm 3+ @NaYF4:Nd 3+ ,Yb 3+ Nanoparticles;
[0012] The NaYF4:Yb 3+ ,Tm 3+ @NaYF4:Nd 3+ ,Yb 3+ The nanoparticles are NaYF4:Nd 3+ ,Yb 3+ Nanoparticles and the NaYF4:Yb 3+ ,Tm 3+ The nanoparticles are obtained by composite reaction;
[0013] The NaYF4:Yb 3+ ,Tm 3+ The nanoparticles are obtained by co-precipitation reaction of a sodium-containing alkaline compound, NH4F, 1-octadecene, oleic acid, a yttrium source, a ytterbium source and a thulium source;
[0014] The NaYF4:Nd 3+ ,Yb 3+The nanoparticles are obtained by co-precipitation reaction of a sodium-containing alkaline compound, NH4F, 1-octadecene, oleic acid, a yttrium source, a ytterbium source and a neodymium source.
[0015] Furthermore, the sodium-containing alkaline compound is NaOH; the yttrium source is YCl3; the ytterbium source is YbCl3; the thulium source is TmCl3; and the neodymium source is NdCl3.
[0016] Furthermore, the method for preparing the methacrylylated gelatin includes the step of reacting gelatin with methacrylic acid in a light-proof manner to obtain the methacrylylated gelatin.
[0017] Furthermore, the temperature of the light-proof reaction is 50° C. and the time is 2 hours.
[0018] Furthermore, the solvent is water.
[0019] The present invention also provides a near-infrared photopolymerizable composite hydrogel prepared according to the above preparation method.
[0020] The present invention also provides application of the near-infrared photopolymerizable composite hydrogel in preparing wound dressings.
[0021] The present invention also provides a wound dressing, comprising the above-mentioned near-infrared light-polymerized composite hydrogel.
[0022] The present invention discloses the following technical effects:
[0023] The present invention combines methacrylated gelatin (GelMa) with upconversion nanoparticles (UCNPs) to form a corresponding near-infrared light-activated upconversion composite hydrogel, that is, a composite hydrogel driven by 808nm near-infrared light. Based on the anti-Stokes energy transfer process of rare earth upconversion materials, near-infrared light excites the rare earth upconversion nanoparticles in the hydrogel, and the luminescent ions therein emit ultraviolet light that can be absorbed by the photoinitiator, thereby curing the composite hydrogel and achieving the purpose of promoting the repair of deep tissue trauma.
[0024] The present invention solves the technical problems that the current hydrogel is limited by the low penetration of ultraviolet light polymerization and the high photothermal effect produced by 980nm polymerization, and provides a new research idea for promoting the repair of deep wound defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 Schematic diagram of the synthesis of composite hydrogel;
[0027] Figure 2 Schematic diagram of the action mechanism of the composite hydrogel UC-YT@NY+GelMa;
[0028] Figure 3 GelMa, composite hydrogel UC-YT+GelMa(NaYF4:Yb 3+ ,Tm 3+ +GelMa) and UC-YT@NY+GelMa(NaYF4:Yb 3+ ,Tm 3+ @NaYF4:Nd 3+ ,Yb 3+ +GelMa) and the scanning distribution of doping elements (O, C, N, Na, F, Nd and Tm);
[0029] Figure 4 FT-IR analysis diagrams of UC-YT, UC-YT@NY, GelMa and UC-YT@NY+GelMa;
[0030] Figure 5 The fluorescence emission spectra of rare earth nanomaterials UC-YT and UC-YT@NY and the absorption spectrum of photoinitiator LAP;
[0031] Figure 6 UC-YT+GelMa and UC-YT@NY+GelMa hydrogels were heated in PBS buffer at high power (1.27 W / cm 2 ) and low power (0.64W / cm 2 ) Temperature change curve after irradiation for 10 minutes;
[0032] Figure 7 Comparison of the photocuring rate-irradiation time of the composite hydrogels UC-YT+GelMa (white column) and UC-YT@NY+GelMa (black column) under the same light power and different near-infrared excitation wavelengths (980nm and 808nm);
[0033] Figure 8 The cross-linking process state diagram of UC-YT+GelMa (980nm irradiation) and UC-YT@NY+GelMa (808nm irradiation) composite hydrogels;
[0034] Fig. 9 808nm (1.27W / cm 2 ) Heat map of UC-YT@NY+GelMa composite hydrogel process (0, 2 and 6 min);
[0035] Fig.10 The temperature variation curve of UC-YT@NY+GelMa irradiated with different power densities at 808nm;
[0036] Fig.11 This is the relationship between the photocuring rate and the 808nm irradiation time;
[0037] Fig.12 It is a statistical graph of the cell absorbance values determined by the MTT method;
[0038] Fig.13 The figure shows the staining results after 48 h of co-culture (scale bar, 10 μm);
[0039] Fig.14 Pictures were taken for cell migration (scale bar, 200 μm);
[0040] Fig.15 Statistical chart of wound conditions and quantitative area size in different treatment groups;
[0041] Fig.16 Schematic diagram of epidermal wound healing model;
[0042] Fig.17 It is the statistical chart of wound healing rate in different treatment groups;
[0043] Fig.18 The pictures of muscle wound healing in mice in different treatment groups (a) and HE pathological staining of striated muscle and skin tissue in tissue defect area (b); the scale bar in a is 5 mm; the scale bar in b is 200 μm;
[0044] Fig.19 This is a thermal image of the repair process of mouse tissue defects irradiated with 808nm;
[0045] Fig. 20 Statistical graph of tissue defect healing rate in different treatment groups at 7 days. DETAILED DESCRIPTION
[0046] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0047] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0048] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0049] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0050] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0051] Example 1
[0052] like Figure 1 As shown, the present invention combines GelMa with UCNPs to form a corresponding near-infrared light-activated upconversion composite hydrogel, that is, a composite hydrogel driven by 808nm near-infrared light, and its mechanism of action is as follows Figure 2 The details are as follows:
[0053] 1. Materials required for the experiment
[0054] 1-Octadecene (C 18 H 36 ), oleic acid (C 18 H 34 O2), yttrium chloride hexahydrate (YCl3·6H2O), ytterbium chloride hexahydrate (YbCl3·6H2O), thulium chloride hexahydrate (TmCl3·6H2O), neodymium chloride hexahydrate (NdCl3·6H2O), ammonium fluoride (NH4F), sodium hydroxide (NaOH), polyacrylic acid (PAA) (C3H4O2) 50% aqueous solution, methanol (CH3CH), tetrafluoroborate nitroso (NOBF4), N,N-dimethylformamide (C3H7NO), acetone (C3H6O), toluene (C7H8), cyclohexane (C6H 12 ), anhydrous ethanol (C2H6O), methacrylic acid (MAA), phosphate buffered saline (PBS), gelatin (Geltain, brand Aladdin, product number G108395).
[0055] 2. Preparation method of composite hydrogel
[0056] (1) Preparation of rare earth upconversion luminescent materials
[0057] Upconversion nanoparticles were synthesized by coprecipitation. Rare earth chlorides easily absorb water in the air, and were prepared into a 0.2 mmol / mL solution for use. TmCl3·6H2O required a smaller amount, and was prepared into a 0.02 mmol / mL solution for use.
[0058] Synthesis of NaYF4:Yb 3+ ,Tm 3+ The experimental steps of (UC-YT) are as follows:
[0059] 1) YCl3 solution (3.975 mL, 0.795 mmol), YbCl3 solution (1 mL, 0.2 mmol) and TmCl3 solution (0.4 mL, 0.005 mmol) were mixed in a 100 mL three-necked flask and heated to 130 °C for 1 h to evaporate the water.
[0060] 2) After cooling to room temperature, add 10 mL of oleic acid (OA) and 15 mL of 1-octadecene (ODE), stir to mix, and heat to 150° C. under N2 atmosphere to completely dissolve the powder.
[0061] 3) At 50°C, a methanol mixture containing 10 mL of NH4F (0.148 g) and NaOH (0.1 g) was added dropwise to the reaction solution, and the reaction system was kept at 50°C for 40 min. The temperature was then raised to 100°C and kept for 1 h to remove methanol.
[0062] 4) Connect a double-row gas device, evacuate for 30 minutes to remove moisture, then turn off the vacuum pump and pass N2, quickly raise the temperature to 300°C and maintain for 90 minutes to obtain nanoparticles.
[0063] 5) Stop the reaction and cool to room temperature, add anhydrous ethanol to precipitate particles, centrifuge at 6000r / min for 5 minutes, discard the supernatant, and dissolve the product with cyclohexane. Wash the precipitate three times and disperse the product in 10mL cyclohexane solution.
[0064] Synthesis of NaYF4:Yb 3+ ,Tm 3+ @NaYF4:Nd 3+ ,Yb 3+ (UC-YT@NY) experimental steps:
[0065] Synthesis of core-shell nanoparticles NaYF4:Yb 3+ ,Tm 3+ @NaYF4:Nd 3+ ,Yb 3+The (UC-YT@NY) process is similar to the above-mentioned method for synthesizing UC-YT. 3+ ,Yb 3+ (50%, 10%) ratio was added, and 0.5mmol NaYF4:Yb synthesized in the previous step was added at 50℃. 3+ ,Tm 3+ The subsequent steps were the same as those of UC-YT to obtain the product, which was dissolved in 10 mL of cyclohexane.
[0066] (2) Preparation of GelMa precursor hydrogel
[0067] 1) Place a heating plate in a fume hood and preheat to 50°C. Dissolve 15 g of gelatin in 150 mL of PBS and stir until the gelatin particles are completely dissolved.
[0068] 2) 12 mL of MAA solution was added dropwise, and the mixed emulsion was allowed to react at 50°C in the dark for 2 h to generate GelMa. To stop the reaction, 150 mL of PBS was preheated to 50°C in advance, added to the above mixed solution, and stirred for 2 h.
[0069] 3) Cut the dialysis membrane into appropriate size and immerse it in distilled water to soften it. Then use a funnel to put the diluted GelMa into the dialysis bag, and fill each bag with about two-thirds of the volume. After sealing the mixed solution, put the dialysis bag in 40℃ deionized water in the dark for 7 days. Change the water twice a day (preheating is required to achieve better dialysis effect). Before each water change, turn the dialysis bag upside down several times to remove the unreacted toxic MAA and low molecular weight impurities.
[0070] 4) The dialyzed reaction product was poured into a Buchner funnel, connected to a circulating water vacuum pump, and filtered twice. The liquid GelMa was then dispensed into centrifuge tubes and stored at -20°C overnight.
[0071] 5) The final sample was placed in a -40°C freeze dryer for 2 days to remove moisture and refrigerated for later use.
[0072] (3) Preparation of composite hydrogels UC-YT+GelMa and UC-YT@NY+GelMa
[0073] The synthesized upconversion nanoparticles are oil-soluble. As biomaterials, they are required to have better hydrophilicity and suitable functional surface groups to enable them to bind with active biomolecules. The surface of the nanoparticles needs to be modified to obtain fluorescent nanoparticles that are biocompatible without affecting the luminescence efficiency.
[0074] After functionalizing the particle surface by organic ligand exchange method, upconversion composite hydrogel was prepared:
[0075] 1) Weigh 1 mg of NOBF4 solid particles and dissolve them in 10 mL of N,N-dimethylformamide (DMF) solution. Add 1 mL of upconversion nanoparticles dissolved in cyclohexane to 2 mL of the prepared NOBF4 solution and dissolve them by ultrasonication for 10 min.
[0076] 2) Add 3 mL of cyclohexane and 3 mL of toluene and centrifuge at 8000 r / min for 10 min. The resulting precipitate is dispersed in 5 mL of DMF solution. Then, 200 mg of polymer PAA is added dropwise. The solution is heated to 80°C and reacted for 1 h. After the reaction is completed, it is cooled to room temperature. The reactant is taken and an excess of acetone is added and centrifuged at 6000 r / min for 5 min.
[0077] 3) Dissolve in 1 mL of ultrapure water and then add anhydrous ethanol, repeat this step twice, and finally disperse the collected rare earth upconversion nanoparticles in 1 mL of ultrapure water.
[0078] 4) Take 1 mL of hydrophilic upconversion nanoparticles UC-YT and UC-YT@NY, add 0.2 g of dry GelMa, mix well, and dissolve to form upconversion composite hydrogels UC-YT+GelMa and UC-YT@NY+GelMa.
[0079] 3. Main methods of material characterization
[0080] (1) Scanning electron microscopy
[0081] The sample to be tested is sprayed with gold and then placed directly under the electron gun. Its surface characteristics are observed on a computer by adjusting parameters such as voltage, spot size, and brightness.
[0082] (2) Fluorescence spectrum test
[0083] Using the steady / transient spectrometer FLS1000 produced by Edinburgh Company, the synthetic up-conversion luminescent material liquid sample was dropped into a quartz cuvette and placed in the spectrometer sample compartment. The near-infrared light source (980nm and 808nm) was selected, the test step size was set to 1nm, and the fluorescence emission spectrum of the sample in the ultraviolet-visible light region was tested.
[0084] (3) Fourier transform infrared spectroscopy test
[0085] Fourier transform infrared testing uses infrared radiation emitted or reflected by a substance to obtain information about the functional groups of the object. After the sample to be tested is dried at 80°C for 10 hours, the sample is mixed with spectral grade potassium bromide (KBr) powder at a mass ratio of 1:150 and ground evenly. The sample is pressed into a thin and hard disc using a tablet press and placed in the sample compartment of a Fourier transform infrared (FT-IR) spectrometer for testing and analysis of the functional groups of each sample. The scanning resolution is 2 cm -1, wave number range is 500cm -1 Up to 4000cm -1 .
[0086] (4) UV-visible absorption spectrum test
[0087] The UV-Vis spectrophotometer can measure the absorption of light of different wavelengths after passing through a sample, and measure the absorption spectrum according to the different absorption degrees of the sample to a certain wavelength of light. Dilute the sample to a suitable concentration, transfer an appropriate amount to a quartz cuvette with a pipette, and use a UV spectrophotometer to detect the absorption spectrum. The wavelength range is 200nm to 750nm.
[0088] (5) Exploration of the relationship between laser power and curing rate
[0089] The prepared upconversion composite hydrogel NaYF4:Yb 3+ ,Tm 3+ +GelMa(UC-YT+GelMa) and NaYF4:Yb 3+ ,Tm 3+ @NaYF4:Nd 3+ ,Yb 3+ +GelMa (UC-YT@NY+GelMa) were mixed with 0.5wt% photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphonate (LAP) to form a hydrogel mixture. 50μL of the composite hydrogel mixture was injected into the customized circular glass hole using a medical syringe. The laser (980nm and 808nm) was used as an excitation light source to irradiate the hydrogel mixture, observe the curing effect of the upconversion composite hydrogel, and use a FOTRIC 280 thermal imager to take pictures and record the temperature.
[0090] 4. In vitro cell experiments
[0091] Cell culture: Take the frozen mouse epithelial fibroblast L929 cells out of the -80℃ biological refrigerator and immediately put them into a 37℃ water bath, gently shaking to accelerate thawing. Wipe the outside of the bottle and transfer it to a sterile operating table. Before opening the bottle cap, disinfect the bottle mouth with an alcohol lamp flame. Add 37℃ preheated DMEM culture medium containing 10% FBS and 1% penicillin-streptomycin to the bottle and transfer it to a 15mL centrifuge tube, 1000r / min, centrifuge for 3 minutes, discard the supernatant, add culture medium to resuspend the cells, and then transfer to a carbon dioxide incubator (37℃, 5% CO2) to culture the cells to allow them to grow adherently, and observe the cell morphology using a fluorescence microscope.
[0092] Cytotoxicity test: The MTT method was used to quantitatively determine the in vitro cytotoxicity of the photopolymerized hydrogel UC-YT@NY+GelMa. 100 μL of L929 cell suspension (5000 cells / well) was inoculated into a 96-well plate and placed in an incubator overnight. Then, 100 μL of upconversion nanoparticles UC-YT@NY and UC-YT@NY+GelMa hydrogel extracts of different concentrations (1%, 5%, 10%, 20% and 40%) were added to the wells of the culture plate. Six replicate wells were set up in each group, and the unadded DMEM culture medium was used as the control group. After 24 hours of culture, the cell growth morphology and morphology were observed under a microscope, 10% MTT solution was added to each well, and 150 μL DMSO was added to each well after incubation in the dark for 4 hours. The cells were shaken on a shaker for 20 minutes, and the absorbance value of the cells was detected using an enzyme marker.
[0093] Cell live / dead staining: Add culture medium containing different concentrations of YT@NY+GelMa hydrogel (0, 1%, 5%, 10%, 20% and 40%) to a 12-well plate containing 1 mL of L929 cell suspension (20,000 cells / well). After 2 days, remove the original culture medium, wash twice with PBS buffer, and observe the cells under a microscope. After 48 hours of culture, trypsinize the cells and collect the precipitate and resuspend the cells. First, add Calcein-AM in the live / dead staining kit to blow the cells evenly, incubate in a CO2 incubator at 37°C in the dark for 20 minutes, then add PI reagent to stain the cells, incubate for 5 minutes in the dark and take them to a microscope (Zeiss-AxioObserver) to capture the fluorescent image of the sample.
[0094] Cell scratch test: L929 cells in the growth phase were digested with trypsin to form a single cell suspension, inoculated in a 6-well plate and cultured normally for 1 day until the cells adhered to the wall. A straight line was drawn on the cell layer with the tip of a sterilized pipette, and then the cells were washed twice with PBS and photographed under a microscope. After adding an appropriate amount of DMEM medium mixed with different volume fractions of UC-YT@NY+GelMa hydrogel, the migration of L929 cells was observed using an inverted fluorescence microscope after another 24 hours of culture.
[0095] 5. Skin trauma repair application
[0096] (1) Rat full-thickness skin wound model
[0097] After depilation and anesthesia, SD male rats (250 g) were anesthetized and full-thickness skin injuries (7 mm in diameter) were made on their backs. All rats were divided into three groups (n=3), and the back wounds were treated differently: a control group with saline, a UC-YT@NY+GelMa hydrogel group without light, and a UC-YT@NY+GelMa group irradiated with a near-infrared laser (808 nm). The injected composite hydrogel mixture contained a photoinitiator, LAP. The wound healing was observed and photographed on different days. The wound area was measured and analyzed using Image J software, and the wound healing rate was statistically analyzed. The formula for calculating the wound healing rate is as follows: Wound healing rate = wound area on the nth day / wound area on the 0th day × 100%.
[0098] (2) Deep tissue wound defect model
[0099] Eight-week-old BALB / c female mice were anesthetized as Fig.16 As shown, an incision was made on the back, and then a 5mm diameter and 3mm deep muscle wound was cut on the muscle with a scalpel and dissecting tools. The wound position was recorded with a marker and the skin was quickly sutured (n=3). After the physiological state of the mouse was stable, 50μL of UC-YT@NY+GelMa composite hydrogel mixed with photoinitiator LAP (0.5wt%) was added to the wound using a medical needle. Different treatments were performed on it: the mouse wound was irradiated with 365nm and 808nm for 10min as the experimental group, and the control group was not treated. Photos of the wound were taken on different dates to observe the wound healing.
[0100] Wound tissues of mice were collected two weeks later and fixed in 4% paraformaldehyde for 2 days, dehydrated with graded alcohol concentrations (30%, 50%, 60%, 70%, 90% and 100%), and then embedded in paraffin. The tissue slices were cut into 5 μm thick tissue sections with a tissue slicer and stained with hematoxylin-eosin (H&E).
[0101] 6. Results and Analysis
[0102] The basic structure of the composite hydrogel formed after adding upconversion nanoparticles UC-YT and UC-YT@NY is similar to that of the precursor GelMa, both of which are porous and uniform honeycomb. From the perspective of pores, the GelMa structure is the loosest, while the hydrogel containing upconversion nanoparticles has smaller pores and is more densely connected to each other. This may be because the addition of UCNPs increases the cross-linking density between GelMa molecular chains, increases the chance of cross-linking between GelMa molecular chains, and plays a role similar to that of a cross-linking agent, thereby improving the cross-linking efficiency between macromolecules. Figure 3The surface scanning distribution of O, C, N, Na, F, Nd, and Tm doping elements is clearly shown in the figure, indicating that all elements are well distributed and the UC-YT@NY+GelMa composite hydrogel is successfully synthesized.
[0103] Fourier transform infrared spectroscopy (FT-IR) can be used to understand the chemical structure of a substance and determine the type of chemical group in the substance based on the position of the peak in the data. Upconversion nanoparticles are -1 Up to 4000cm -1 Fourier transform infrared spectra in the range of ( Figure 4 ), UC-YT and UC-YT@NY have similar absorption bands at 2580 cm -1 and 1586cm -1 At 1654cm -1 The peak at 3248 cm indicates the presence of C=O groups in the GelMa system. -1 The amide A band is mainly caused by the stretching vibration of NH in GelMa. -1 The broad single-line peak nearby comes from the stretching vibration of hydroxyl (-OH), which also proves that the hydrogel has good hydrophilicity. Since PAA has abundant carboxyl groups on its surface and organic GelMa has amino groups on its surface, hydrophilic upconversion nanoparticles can be dissolved with it.
[0104] like Figure 5 As shown in the figure, both rare earth upconversion nanoparticles UC-YT and UC-YT@NY show the ability of upconversion luminescence. Generally speaking, the emission spectrum of the light source and the absorption curve of the material with light response function should match within a certain range. The emission spectrum of the rare earth upconversion luminescent particles in aqueous solution coincides with the absorption spectrum of the photoinitiator LAP, which lays a theoretical foundation for near-infrared photopolymerization: the active photoinitiator can effectively utilize the Tm from the upconversion mechanism. 3+ Ultraviolet radiation causes LAP to produce free radicals, which react with the double bond groups in GelMa to eventually form polymerized long-chain compounds.
[0105] like Figure 6 As shown in the figure, the temperature increases with the increase of laser power and reaches a stable state within 10 minutes. 2 After 10 minutes of 980nm laser irradiation on UC-YT+GelMa, the temperature of the hydrogel rose by 23°C, while the temperature of the UC-YT@NY+GelMa hydrogel sample after 808nm laser irradiation only increased by 12°C compared with the initial temperature, which indicates that the latter has a smaller photothermal effect.
[0106] The present invention compares the performance of 980nm and 808nm lasers at low power (0.64W / cm 2 ) and high power (1.27W / cm 2 ) driven by the composite hydrogel. It is worth noting that the higher the power of the light source, the higher the curing rate under the same conditions. The upconversion composite hydrogel synthesized according to the present invention has a higher photopolymerization efficiency driven by 808nm than that of the 980nm group ( Figure 7 ).
[0107] Studies have shown that hydrogels can effectively seal wounds and promote tissue regeneration due to their excellent adhesion properties. In the present invention, the morphology of the hydrogel also changes during the chemical cross-linking reaction induced by two near-infrared laser irradiations. Figure 8 , the 808nm-driven UC-YT@NY+GelMa hydrogel first formed a gel state, and with the passage of time, its viscous, stringy morphology became more and more obvious, which highlighted the excellent adhesion properties of the composite hydrogel.
[0108] In order to make subsequent biological experiments easier to carry out, the present invention selects Nd 3+ The composite hydrogel UC-YT@NY+GelMa, which can be excited by 808nm, explores the relationship between its light power, temperature and curing rate. The hydrogel is mixed with the photoinitiator LAP and irradiated with lasers of different powers to achieve photopolymerization. The temperature change during the photocuring process is observed by a thermal imaging camera ( Fig. 9 ).
[0109] As the power increases, the temperature of the photoresponsive hydrogel increases. 2 When the temperature exceeds 60℃, there is a trend of continuous temperature rise ( Fig.10 ). It is speculated that the reason for this phenomenon is that the Nd 3+ After receiving 808nm laser, more energy is transferred to Yb 3+ The large amount of water molecules in the composite hydrogel UC-YT@NY+GelMa are 3+ When energy is absorbed, it causes the temperature of the entire system to rise. To ensure the appropriate temperature range, we chose 1.27W / cm 2 After 8 min, the curing rate of the composite hydrogel reached about 96.28% ( Fig.11 ).
[0110] After preliminary experiments and comparative analysis with hydrogels polymerized at 980nm, it was found that the hydrogel driven by 808nm not only has a higher photocuring rate, but also has an adjustable temperature range caused by the photothermal effect, and possesses basic properties for biological applications. Good biocompatibility is a prerequisite for the application of hydrogels in tissue engineering. Vascular damage caused by trauma has a serious probability of morbidity and risk of death. The healing mechanisms of animals and humans are similar, and modeling them can reflect the therapeutic effects of living bodies to a certain extent. The in vivo models of the present invention include a skin surface wound model and a deep tissue defect model in the body. The hydrogel that can respond to 808nm is injected into the wound as a dressing, and the wound healing conditions of each group are observed and compared.
[0111] from Fig.12 It can be seen that the addition of upconversion nanoparticles alone will cause the cell absorbance values to be lower than that of the control group, which is slightly toxic to the cells. However, after adding the photopolymerized hydrogel mixture containing organic substances GelMa, the absorbance values of cells in each group exceeded that of the control group, while maintaining normal cell morphology. This shows that the composite hydrogel UC-YT@NY+GelMa has no toxic side effects and can improve cell viability to a certain extent, because the three-dimensional structure of the hydrogel provides a favorable microenvironment for cell growth and differentiation, thereby reducing cytotoxicity. Studies have also shown that hydrogels with high porosity can support the diffusion of oxygen and nutrients to cells and excrete waste from the matrix.
[0112] Live / dead staining experiments more intuitively reflect the cell compatibility of UC-YT@NY+GelMa hydrogel. After the hydrogel and cells were co-cultured for 48 hours, the Fig.13 As shown, compared with the control group, all cells in the hydrogel additives of different components were stained green, almost no red dead cells were detected, and the number of cells in the experimental group showed an increasing trend. Different components of UC-YT@NY+GelMa hydrogel additives promoted cell proliferation. This may be related to the adhesion sites for cell proliferation in the modified gelatin. This is consistent with the results of the cytotoxicity test, further showing that the hydrogel has excellent biocompatibility and meets the safety requirements as a wound dressing.
[0113] like Fig.14 As shown, L929 cells were co-cultured with different concentrations of composite hydrogel extracts (1, 5, 10, 20 and 40%). After 24 hours of incubation, live cells migrated to the scratch, and the number of cells at the scratch in the experimental group was higher than that in the control group. The results showed that the hydrogel extract did not affect the migration of L929 cells. Because UC-YT@NY+GelMa retains the properties of gelatin and contains various active groups on its side chains, such as amino, carboxyl and hydroxyl groups, to improve cell viability, and the interconnected pores between hydrogels can promote cell migration, which shows that it has the conditions for use as a wound dressing.
[0114] like Fig.15 As shown, within 14 days, the wound area of all groups gradually decreased over time, and the best wound healing effect was achieved under near-infrared excitation. The wound area on days 3, 7, 10, and 14 was quantified, and the changes in the wound healing process were recorded and analyzed. Specifically, in terms of the quantitative wound area on days 3 and 7, the near-infrared group showed a 35.4% and 48.2% decrease compared to day 0, respectively, which was significantly higher than the hydrogel group (35% on day 3 and 41.8% on day 7) and the control group (26.3% on day 3 and 37.9% on day 7). Similarly, the best wound healing was found in the near-infrared group on day 14, with a wound healing rate of 88.2%, while the other two groups were both below 80% ( Fig.17 UC-YT@NY+GelMa uses 808nm laser to stimulate the upconversion luminescence process, which promotes Tm 3+ The ions emit ultraviolet light. The photoinitiator LAP absorbs Tm 3+ The ultraviolet light emitted polymerizes the GelMa gel monomers. As a result, an adhesive gel is formed on the surface of the wound skin to block the invasion of external bacteria. The wound healing rate of the composite hydrogel polymerized at 808nm is higher than that of the control group and the group with near-infrared hydrogel. Because near-infrared light is used in the process of hydrogel formation in vivo, the damage of ultraviolet rays to cells can be reduced.
[0115] like Fig.18 As shown in Figure a, the hydrogel solidification on the mouse muscle wound at 7 days showed differences, and the wound closure of the 808nm treatment group was significantly improved compared with the other groups. Tissues were collected two weeks after surgery for hematoxylin-eosin (H&E) staining to further evaluate the degree of wound healing, inflammation, and granulation tissue levels ( Fig.18 b). It can be observed that the pathological sections of mouse striated muscle regenerated normally. It is worth noting that the healing effect of the 808nm irradiation group was the best, with a more complete epidermal structure, more hair follicles, and the thickest regenerated epithelial tissue (arrow in the figure).
[0116] Fig.19 It was shown that under near-infrared laser irradiation, the body temperature of mice remained within the normal physiological range. Thanks to the high porosity of hydrogels, they have the potential to absorb excess tissue exudates and transport water vapor, and the interconnected pores can promote cell migration and angiogenesis. Therefore, the 808nm responsive composite hydrogel UC-YT@NY+GelMa can effectively accelerate the repair of deep tissue wounds.
[0117] like Fig. 20As shown in the figure, the in vivo healing rate of wounds irradiated with near-infrared lasers exceeded 70%, which was much higher than the wound healing rates of the untreated control group (36.5%) and ultraviolet light irradiation (39.5%). This is because the 808nm near-infrared has deep tissue penetration, which can promote cell migration and extracellular matrix deposition.
[0118] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a near-infrared photopolymerized composite hydrogel, It is characterized in that The method comprises the steps of uniformly mixing hydrophilic upconversion nanoparticles and methacrylated gelatin in a solvent to obtain the near-infrared photopolymerization composite hydrogel.
2. The preparation method according to claim 1, It is characterized in that The hydrophilic upconversion nanoparticles are prepared by mixing the upconversion nanoparticles with NOBF 4 Contact reaction is performed to obtain.
3. The preparation method according to claim 2, It is characterized in that The upconversion nanoparticles are NaYF 4 :Yb 3+ ,Tm 3 + Nanoparticles or NaYF 4 :Yb 3+ ,Tm 3+ @NaYF 4 :Nd 3+ ,Yb 3+ Nanoparticles; The NaYF 4 :Yb 3+ ,Tm 3+ @NaYF 4 :Nd 3+ ,Yb 3+ The nanoparticles are NaYF 4 :Nd 3+ ,Yb 3+ Nanoparticles and the NaYF 4 :Yb 3+ ,Tm 3+ The nanoparticles are obtained by composite reaction; The NaYF 4 :Yb 3+ ,Tm 3+ Nanoparticles are sodium-containing alkaline compounds, NH 4 F, 1-octadecene, oleic acid, yttrium source, ytterbium source and thulium source are obtained by co-precipitation reaction; The NaYF 4 :Nd 3+ ,Yb 3+ Nanoparticles are sodium-containing alkaline compounds, NH 4 F, 1-octadecene, oleic acid, yttrium source, ytterbium source and neodymium source are obtained by co-precipitation reaction.
4. The preparation method according to claim 3, It is characterized in that The sodium-containing alkaline compound is NaOH; the yttrium source is YCl 3 ; The ytterbium source is YbCl 3 ; The thulium source is TmCl 3 ; The neodymium source is NdCl 3 .
5. The preparation method according to claim 1, It is characterized in that The method for preparing the methacrylylated gelatin comprises the steps of reacting gelatin with methacrylic acid in the dark to obtain the methacrylylated gelatin.
6. The preparation method according to claim 5, It is characterized in that The temperature of the light-proof reaction is 50° C. and the time is 2 hours.
7. The preparation method according to claim 1, It is characterized in that The solvent is water.
8. A near-infrared photopolymerized composite hydrogel prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of the near-infrared photopolymerizable composite hydrogel as claimed in claim 8 in preparing wound dressings.
10. A wound dressing, It is characterized in that It includes the near-infrared photopolymerized composite hydrogel as described in claim 8.
Citation Information
Patent Citations
Water-soluble up-conversion nanoparticles and preparation method thereof
CN104371727A
Near-infrared dye-sensitized rare earth luminescent multilayer core-shell structure material hybrid system material as well as preparation method and application of near-infrared dye-sensitized rare earth luminescent multilayer core-shell structure material hybrid system material
CN114231273A
Rare earth doped light switchable up-conversion nano-composite particle as well as preparation method and application thereof
CN116463115A
Up-conversion resin composite slurry for 3D printing and near-infrared laser curing forming method
CN116785497A
Cited By
Zinc sulfide modified hydrogel with near-infrared light responsiveness-photothermal effect as well as preparation method and application of zinc sulfide modified hydrogel
CN120053757A
